Lifnim mišurat ha-din ir derekh erec problema, arba etikos paieškos žydų tradicijoje ir Vilniaus Gaono kranklys = The Problem of Lifnim Mishurat Hadin and Derekh Eretz : In Search of Ethics in the Jewish Tradition and the Raven of the Gaon of Vilna - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English]The problem analyzed in this article can be formulated as a question: do ethics, for the Gaon of Vilna, exist outside the Torah and Halakha? This question particularizes and analyzes the more general question posed by R. Aharon Lichtenstein in one of his articles, particularly Does Jewish Tradition Recognize an Ethic Independent of Halakha?, and presents arguments that the traditional Jewish notions lifnim mišurat ha-din and derekh erec, which a number of contemporary scholars of Jewish studies associate to an ethical impulse possibly coming from outside, remain rooted in the Torah and Halakha in the case of the Gaon of Vilna. It is based on both the legendary image of the Gaon of Vilna and the interpretations of agada attributed to him as well as derived from his customs. Through these aspects, an unconditional devotion of the Vilnius Gaon to the study of the Torah, superseding all other possible choices of virtue, can be highlighted. Concerning his customs, which often outweigh the demands of the Halakha, it would be quite problematic to find in them any ethical or social concern. While discussing the theme of animals, which was presented as an argument by R. A. Lichtenstein in finding a positive attitude to an ethical source outside the Torah or Halacha in the Jewish tradition (such as taking an example of proper behavior from a cat, rooster, or ants, as has been taught by some sages of the Talmud), it is argued that the images of animals, as far as examples for proper behavior, are too contradictory in the broader context of the Torah and Talmud: first, in the Torah, some examples of animals are referred to as possible examples; such reference thus do not go beyond the Torah. Second, in the Torah and Talmud, the images of and attitudes toward those animals (especially cats, but also dogs) are quite contradictory. Third, with regard to the Gaon of Vilnius, the animals were only images that allowed him to emphasize certain features and behavioral guidelines necessary for studying and practicing the Torah, but not as examples of ethical behavior.